Transformational adaptation for Africa: Framing, opportunities, and recommendations for negotiators at SB62 - Dampha, N.K.; Adhiambo, P.; Mukherji, A.; Koren, J.; Manyame, W.D.; Zvobgo, L.; Emiru, N.; Williams, P.A.; Bakhiet, A.; Awolala, D.O.; Denje, T.M.; Abbas, A.; et al. (2025)
In Africa, where climate risks are intensifying and existing adaptation strategies often prove insufficient, there is an urgent need to combine incremental and transformational approaches as a pathway toward long-term resilience and sustainable development. However, transformational adaptation remains a relatively new and evolving concept, with limited consensus on its definition, scope, application, and metrics. As global attention on transformational adaptation continues to grow within United Nations Framework Convention on Climate Change (UNFCCC) processes, including through the Global Goal on Adaptation (GGA), it is essential that African negotiators are well equipped to engage in this dialogue and articulate Africa’s perspectives on its meaning, principles, opportunities, and constraints. This briefing paper synthesises key conceptual frameworks on transformational adaptation, captures insights from African experts, and offers recommendations and opportunities to strengthen Africa’s engagement in this emerging discourse.